Introducing Solid Foods to Infants in the Asia Pacific Region - Inoue, Madoka; Binns, Colin (MDPI Publishing, 2014)
For infants’ optimal growth and development, the introduction of nutritionally suitable solid foods at the appropriate time is essential. However, less attention has been paid to this stage of infant life when compared with studies on breastfeeding initiation and duration. The practice of introducing solid foods, including the types of foods given to infants, in the Asia Pacific region was reviewed. In total nine studies using the same questionnaire on infant feeding practices were analysed to gain a better understanding of trends in the introduction of solid foods in this region. All studies showed less than optimal duration of exclusive breastfeeding indicating an earlier time of introduction of solid foods than recommended by the WHO. Most mothers commonly used rice or rice products as the first feed. In many studies, the timing of introducing solid foods was associated with breastfeeding duration. Compared with the Recommended Nutrient Intakes for infants aged above six months, rice/rice products are of lower energy density and have insufficient micronutrients unless they have been fortified. Although the timing of introducing solid foods to infants is important in terms of preventing later health problems, the quality of the foods should also be considered. Recommendations to improve the introduction of solid foods include measures to discourage prelacteal feeding, facilitating breastfeeding education and providing better information on healthier food choices for infants.